A Companion to Late Antique and Medieval Islamic Cordoba
1 online resource
Keywords: A Companion to Late Antique and Medieval Islamic Cordoba cover the history and culture of Roman, late antique, Visigoth and al-Andalus Cordoba in nineteen contributions, from the foundation of the city in the 169/168 B.C. by the praetor Marcus Claudius Marcellus to the end of the Muslim period in 1236 B.C., when the city fell into the hands of Ferdinand III the Saint, King of Castile. Making use of archaeological data and historical sources, combined with the latest research on the various fields under study, its authors give a compelling account of Cordoba’s most important archaeological, urban, political, legal, social, cultural and religious facets throughout the most exciting fifteen centuries of the city.